26. THE KNOWLEDGE ABOUT BLOOD TRANSFUSION SAFETY OF NURSES AT THE NATIONAL LUNG HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluated nurses’ knowledge of blood transfusion safety at the National Lung Hospital in 2022. Methods: Cross-sectional study. Results: Research conducted on 246 nurses working in 15 clinical departments of the National Lung Hospital showed that 82% of nurses answered correctly all 10 questions about blood transfusion safety. 96% of nurses answered correctly the question about temperature to preserve red blood cells. 3% of nurses incompletely answered the question about the time allowed for plasma transfusion after defrosting. 97% of nurses answered correctly about complications that can occur during blood transfusion. Risk factors causing unsafety in blood transfusion: 5% of nurses checked incomplete information about blood delivery. 2% of nurses did not handle blood transfusion abnormalities correctly. Conclusion: The knowledge about safety of nurses was still limited. Therefore, it is necessary to regularly re-training on blood transfusion safety.
Keywords: Knowledge, blood transfusion safety, Nurses.